Towards precise ages and masses of Free Floating Planetary Mass Brown Dwarfs - Canty, J; Lucas, P; Roche, P; Pinfield, D (2013)
Measurement of the substellar initial mass function (IMF) in very young clusters is hampered by the possibility of the age spread of clustermembers. This is particularly serious for candidate planetary mass objects (PMOs), which have a very similar location to older and more massive brown dwarfs on the Hertzsprung-Russell Diagram (HRD). This degeneracy can be lifted by the measurement of gravity-sensitive spectral features. To this end we have obtained mediumresolution (R ~ 5000) Near-infrared Integral Field Spectrometer (NIFS) K-band spectra of a sample of late M-/early L-type dwarfs. The sample comprises old field dwarfs and very young brown dwarfs in the Taurus association and in the σ Orionis cluster. We demonstrate a positive correlation between the strengths of the 2.21 μm Na I doublet and the objects' ages. We demonstrate a further correlation between these objects' ages and the shape of their K-band spectra. We have quantified this correlation in the form of a new index, the H2(K) index. This index appears to be more gravity-sensitive than the Na I doublet and has the advantage that it can be computed for spectra where gravity-sensitive spectral lines are unresolved, while it is also more sensitive to surface gravity at very young ages (<10 Myr) than the triangular H-band peak. Both correlations differentiate young objects from field dwarfs, while the H2(K) index can distinguish, at least statistically, populations of ~1Myr objects from populations of ~10 Myr objects. We applied the H2(K) index to NIFS data for one Orion nebula cluster (ONC) PMO and to previously published low-resolution spectra for several other ONC PMOs where the 2.21 μm Na I doublet was unresolved and concluded that the average age of the PMOs is ~1Myr. © 2013 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.